Penerapan Prinsip Citizen’s Charter Di Kantor Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Gowa - Nirmalasari, Nirmalasari; Setiawati, Budi; Burhanuddin, Burhanuddin (Universitas Muhammadiyah Makassar, 2021)
The study aimed to find out how openness of service, responsiveness, and public complaints about service available at the Office of Investment and Integrated Services of One Door Gowa Regency. This study used descriptive method. The number of informants in this study was 6 people. The results of this study showed that the DPM PTSP of Gowa Regency had hot fully implemented the Citizen’s Charter Principle as Oliver and Drewry’s theory of service oppeness, service responsiveness, and service grievance, because there was no collaboration with independent oversight institutions and sign service Charters; no publication of the complete organizational structure with the names of authorized officials and publication of service fees manually and online; there was no publication of information on performance targets and performance achievements online; did not yet have regulations regarding guaranteeing equal rights for service recipients; there was no collaboration with an independent agency as a mediator between the DPM PTSP GowaRegeny with the service recipient if there was no agreement to resolve complaints.